Application of the Verified Neutron Monitor Yield Function for an Extended Analysis of the GLE # 71 on 17 May 2012 - A. L. Mishev; S. A. Koldobskiy; I. G. Usoskin; L. G. Kocharov; G. A. Kovaltsov (Space Weather)
Abstract Intense solar activity was observed in May 2012. A notable ground level enhancement (GLE) was registered on 17 May 2012 by several space‐borne instruments as well as on ground by neutron monitors (NMs). This event is known as GLE # 71. Here, we derived the spectral and angular characteristics, and apparent source position of the solar protons during the GLE # 71, employing verified newly computed NM yield function and sophisticated unfolding procedure. We considerably improved the previously derived information about the spectra and angular distribution, namely, the precision, time span, and time resolution of the derived characteristics, specifically during the event onset and late phase. A comparison with direct measurements, with the Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics (PAMELA) experiment, of the particle fluence was performed, and good agreement between NM and direct space‐borne data analysis was achieved. Subsequently, we computed the effective dose rates in the polar region at several altitudes during the event using the derived rigidity spectra of the solar protons as a reliable input for the corresponding radiation model. The contribution of the galactic cosmic rays and solar protons to the exposure is explicitly considered. We computed the integrated exposure during the event and discussed the exposure of crew members/passengers to radiation at several altitudes.